Evaluasi Drug Related Problems (DRPS) Pada Pasien Di Ruang Anak Rawat Inap Di Rumah Sakit Imanuel Bandar Lampung Dengan Diagnosa Diare - Saputri, Gusti Ayu Rai; Angin, Martinus Perangin; Fitriana, Ramadhani (Peneliti.net, 2024)
Diarrhea is a disease characterized by an increase in the frequency of defecation more than 3 times a day accompanied by liquid stool consistency and accompanied by the presence or absence of blood or mucus. In the management of diarrhea in toddlers who undergo treatment, it will have an impact on the emergence of problems in drug administration Drug Related Problems (DPRs). The purpose of this study was to determine the characteristics of hospitalized pediatric patients diagnosed with diarrhea, including age, gender and weight grouping, to determine the treatment of diarrhea in pediatric patients at Imanuel Hospital Bandar Lampung in the July- Desember 2022 period including drug classes, to evaluate the management of diarrhea treatment in pediatric patients related to DRPs at the Imanuel Hospital Inpatient Installation in Bandar Lampung in the July-December 2022 period including: Drugs without indication, indication without drug, under dose and over dose. A study wasconducted on diarrhea patients in the children’s room who were treated at the Imanuel Way Halim Hospital inpatients installation from July-December 2022. With retrospective data collection techniques and descriptive analysis, a sample of 46 patients with an age range of 0-12 years was obtained. The results of data collection and processing showed that at the Imanuel Way Halim House, the most common gender was 30 men and 16 women. The most drug therapy received by diarrhea patients is zinc supplement group (71,73%) while other drugs used together with diarrhea drugs for diarrhea therapy are antidiarrheal (56,52%). The evaluation results showed that potential DPRs were drugs without indications (0,00%), indications drugs (2,17%), excessive dose (0,00%), under dose (0,00%).